Mangrove Rehabilitation Action: Growing Hope from the Coast in Tabu Hamlet, Bone Regency, South Sulawesi - Muchtar Amiluddin; Mohammad Roin Najih; Anisa Aulia Sabilah; Irwan; Yasser Arafat; Yakub Suleman; Ismail; Hawati; Khairul Jamil; Awaluddin; Deni Sarianto; Lalu Penta Febri Suryadi (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2026)
Mangrove ecosystems play a critical ecological role in maintaining coastal stability by serving as natural buffers against erosion, storing blue carbon, and providing habitat for marine organisms. In recent years, coastal zones in Bone Regency, South Sulawesi, have been degraded due to anthropogenic activities such as mangrove clearing, land conversion for aquaculture, and coastal infrastructure development. To address this issue, the Politeknik Kelautan dan Perikanan Bone in collaboration with Lembaga Survey Nypah Indonesia conducted a community service activity titled “Mangrove Rehabilitation Action: Growing Hope from the Coastline”. The activity was held on November 8th, 2025, in Tabu Hamlet, Waetuwo Village, Tanete Riattang Timur Sub-district, Bone Regency. Its objectives were to restore the mangrove ecosystem, raise community awareness of environmental conservation, and foster collaboration between vocational education institutions, environmental organizations, and local communities. A total of 100 participants—including students, lecturers, and residents—planted 2,000 seedlings of Rhizophora mucronata and Avicennia marina. The activity improved participants’ understanding of mangrove ecology, strengthened community-academic collaboration, and initiated plans for an eco-education area. This program serves as a participatory model for sustainable coastal ecosystem restoration.